Review Sistematik: Elemen-Elemen Utama dalam Membangun Budaya Keselamatan Pasien di Rumah Sakit - Wibowo, Adik (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2017)
Patient safety culture in a hospital setting is the foundation for all health care activities,with the aim to provide safe and comfortable environment throughout the healing process of the patients. This systematic review aims to describe:1) the relationship between hospital as an organization and patient safety culture,2) the traditional and the modern concepts on patient safety, 3)the seven basic elements as founda tion of hospital patient safety culture and 4) the instrument to analyse hospital patient safety culture. The paradigm has changed from traditional way of punishing hospital staff when doing medical error to the just culture, with the philosophy that hospital system as an organization to some extent could contribute to the errors made by staff. The AHRQ survey further elaborates the seven basic elements of patient safety culture into 12 dimensions and this instrument has been used by hundreds of hospitals.. It is recommended for hospitals to conduct situation analysis on patient safety culture to identify the strengths and the weaknesses as evdence to improve patient safety.